Importance of secretarial profession in promoting effective service delivery in Nigeria - Usioboh, Sunday A.; Akpomudjere, O. (Journal of Professional Secretaries and Office Administrators, 2014)
The quality of service delivery provided by public institution has been assumed to be very poor over the years. Sadly the inefficiency which characterized these services has crept into the private sector. Little wonder the average Nigerian citizen is daily assaulted with poor customer service delivery by operators in almost all sectors of the economy. Attempts have been made to improve quality of service provided by the government to the Nigerian populace over the years. The SERVICOM programme launched by the Federal Government in 2005 was designed to address obvious gaps in service delivery using some selected sectors as pilots. They discovered that many public services were inaccessible, of poor quality and indifferent to customer needs. This paper will examine the importance of secretarial profession in promoting effective service delivery in Nigeria, proffer solutions and recommendations.